‘BIOETHICS’IS SUBORDINATE TO MORALITY IN JAPAN - Tanida, Noritoshi (Bioethics, 1996)
Disputes over brain death and euthanasia are used to illuminate the question whether there really is a Japanese way of thinking in bioethics. In Japanese thought, a person does not exist as an individual but as a member of the family, community or society. I describe these features of Japanese society as‘mutual dependency’. In this society, an act is‘good’and‘right’when it is commonly done, and it is‘bad’and‘wrong’when nobody else does it. Thus, outsiders to this ring of mutual dependency encounter ostracism. One feature of this society is a lack of open discussion which leads to the existence of multiple standards. This Japanese morality even prevails over written laws. In Japan, there is a public stance that euthanasia does not exist. On the other hand, there are certain decisions which have permitted euthanasia. Similarly, organ transplants were performed from brain dead donors, while that procedure was not accepted officially by the medical profession. In this situation, there is a danger that human rights will be neglected. So far bioethical approaches have not helped to work out these problems. This may be because Japanese think that bioethics is subordinate to morality. The current dispute over brain death involves a struggle for the establishment of a rational society in Japan. Overcoming mutual dependency and ostracism is essential to resolve this struggle and to lead Japan into a society of mutual respect where all individuals, families and communities are esteemed.